Kumpulan Cerpen Kampus: Dinamika Kehidupan Mahasiswa; Kilau Mentari di Langit Kampus - Rahayu, Poppy; Septiana, Amelya; J.Noverisa, Eva; Setiawati, Nia; Widijanti, Tasya (Universitas Lampung, 2025)
This Campus Short Story Collection is a persuasive approach in character education, where a college environment can drill various student problems regarding their personal and environmental issues, regarding academic and non-academic issues, through the approach of a literary work, so that it gives rise to a positive mental attitude, namely pouring out the difficulties faced through a work, namely writing campus short stories. Concretely, the purpose of writing a Campus Short Story anthology collaboratively is to find out how to write a Campus Short Story anthology collaboratively, what results are achieved, what concepts are found, and what obstacles are faced in writing a Campus Short Story Collection collaboratively. The results of this study are an anthology of short stories written with full feeling by the authors because they relate to the problems they are facing. The authors realize that they should not get caught up in a problem but can continue to work, for example through writing a short story that can reflect something from whatever is faced.Keywords: Anthology, Short Story, Campus